IPCRF:ANEND TO END INDIAN PAPER CURRENCY RECOGNITION FRAMEWORK FOR BLIND AND VSECURITYIMPAIRED PEOPLE - Mr.P.Rajalingam, ADUSUMALLI LIZY, HANMANOLLA PAVANI, SANGU MOUNIKA (Pegem Journal of Education and Instruction, 2023)
The Indian Paper Currency Recognition Framework (IPCRF) is an innovative system designed to assist blind and visually impaired individuals in identifying Indian currency denominations independently. Leveraging advanced deep learning techniques, the framework employs a hybrid Convolutional Neural Network (CNN) and Long Short-Term Memory (LSTM) architecture to accurately classify currency notes. The system operates offline, ensuring accessibility in areas with limited internet connectivity. By providing audio feedback and tactile cues, IPCRF enhances the autonomy of visually impaired users in financial transactions.